Impact of network topology on the thermal and mechanical properties of lithium germanate glasses. Issue 2 (1st November 2021) - Sørensen, Søren S.; To, Theany; Christensen, Johan F. S.; Johra, Hicham; Smedskjaer, Morten M.
Abstract: In this work, we study the structure–topology–property relations of a series of melt‐quenched lithium germanate glasses. These glasses exhibit the so‐called germanate anomaly, that is, the germanium atoms feature a distribution of four‐coordinated and higher coordinated germanium species, manifesting itself as anomalies in several material properties. Here, we couple variations in the number of atomic bond constraints with measured variations in thermal and mechanical properties, including thermal conductivity, Vickers hardness, and fracture toughness. For thermal conductivity, a strong correlation is found with sound velocity as well as with the volumetric constraint density. For hardness, a good correlation with volumetric constraint density is found, whereas, for fracture toughness, variations in network topology alone are insufficient to explain the composition–property relation. To account for this, we apply a recent model which incorporates knowledge of local structure, mechanical properties, and fracture patterns to predict the fracture toughness, showing a good qualitative agreement with the experimental data.